Analysis of the Crust Deformations before and after the 2008 Wenchuan Ms8.0 Earthquake Based on GPS Measurements - Jicang Wu; Renzhao Liu; Yongqi Chen; Conrad Tang; Guojie Meng; Yaming Dang (International Journal of Geophysics)
We use the movement velocities of GPS stations in western Sichuan province, China, to determine the distribution of horizontal strain accumulation before the 2008 Wenchuan Ms8.0 earthquake with a piecewise approximation approach and the coseismic displacements to determine the fault slips of the earthquake with an inversion analysis method. The results show that the distribution of the principal strain rates is strongly related to the active faults in the region, but along Longmenshan fault where the earthquake occurred, the strain rates are much lower than the others. The fault slip distribution shows mainly a thrusting with dextral striking, and the fault slips in the upper parts of the fault plane are in general bigger. Using the current strain accumulation rate and the released energy by the earthquake, we predict such a big earthquake in Longmenshan fault zone will happen in 460 to 1380 years.